2015
DOI: 10.3122/jabfm.2015.01.140072
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Lung Cancer Outcomes With Targeted Therapies: An Update for Family Physicians

Abstract: In the past decade the advent of target therapy has led to a silent revolution in the treatment of lung cancer. Thanks to the specificity of their target, new tailored drugs are able to achieve a larger benefit and lower toxicity and provide better quality of life than cytotoxic drugs in a limited number of patients, selected by molecular profile. Nowadays, the epidermal growth factor receptor tyrosine kinase inhibitors erlotinib and gefitinib, and the anaplastic lymphoma kinase inhibitor crizotinib, are targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
0
22
0
2
Order By: Relevance
“…Cancers of the lung and bronchus are a set of devastating diseases, which kill 159,260 Americans in 2014(1). Based on etiological and pathological differences, lung cancer can be divided into two major histotypes, namely non-small cell lung cancer (NSCLC) and small-cell lung cancer (SCLC)(2).…”
Section: Introductionmentioning
confidence: 99%
“…Cancers of the lung and bronchus are a set of devastating diseases, which kill 159,260 Americans in 2014(1). Based on etiological and pathological differences, lung cancer can be divided into two major histotypes, namely non-small cell lung cancer (NSCLC) and small-cell lung cancer (SCLC)(2).…”
Section: Introductionmentioning
confidence: 99%
“…Rolfo et al 10 provide an excellent update on the changing fate of lung cancer, and the world of genetics is the reason. Some lung cancers can now be identified by mutations and treated with specific medications.…”
Section: Clinical Cases Conundrums and Reviewsmentioning
confidence: 99%
“…To overcome the challenges with cytotoxic compounds like PAC, targeted therapies and immune checkpoint inhibitors have been developed and approved for NSCLC treatment. However, even with these drugs, it is widely reported that only 60% of NSCLC tumors show targetable mutations and only 25% of patients benefit from immunotherapy [25]. Therefore, there is an unmet need to develop safe and efficacious drugs for the treatment of advanced lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the discovery of molecular mutations that drive the progression of cancers and subsequently the introduction of targeted therapies into clinical practice [14,25]. These targeted therapies interact with specific molecular drivers involved in carcinogenesis, cell proliferation, apoptosis, and metastasis of cancer cells.…”
Section: E F a B Cmentioning
confidence: 99%
See 1 more Smart Citation